Membangun Budaya Lembaga Pendidikan - Sugeng Listyo (UIN Maulana Malik Ibrahim Malang, 2008)
The culture of educational institution is something that is built from the companionship between the values followed by the leader and those followed by the teachers and the staffs. Those values are built by human thought existing in the madrasah (school). The companionship, then, produces the thought of organization which emerges in the form of values to be believed by all members of the institution. Furthermore, those values will be the main medium to shape the culture of its educational institution. The culture then rises in many kinds of visible symbols and acts in the daily life of the educational institution. The concept of building the culture through companioning different values becomes an interesting topic to be explored through this paper. This paper also intends to explore the significance of forming and shaping the thought of organization as the way to lead a harmonious institution atmosphere. Budaya lembaga pendidikan adalah sesuatu yang dibangun dari persahabatan antara nilai-nilai yang diikuti oleh pemimpin dan yang diikuti oleh para guru dan para staf. Nilai tersebut dibangun oleh pemikiran manusia yang ada di madrasah (sekolah). Oleh karena itu, persahabatan menghasilkan pemikiran tentang organisasi yang muncul dalam bentuk nilai yang dapat dipercaya oleh semua anggota institusi. Selanjutnya, nilai tersebut akan menjadi media utama untuk membentuk budaya lembaga pendidikannya. Budaya kemudian meningkat dalam berbagai jenis simbol dan tindakan yang terlihat dalam kehidupan sehari-hari institusi pendidikan. Konsep membangun budaya melalui pendampingan nilai yang berbeda menjadi topik yang menarik untuk dijelajahi melalui makalah ini. Makalah ini juga bermaksud menggali makna pembentukan dan pembentukan pemikiran organisasi sebagai cara untuk memimpin atmosfir institusi yang harmonis.